Intrathoracic Goiter: General Pathologic Considerations - Suiffet, Walter (Cirugía del Uruguay, 1980)
The author's experience with 50 cases of Intrathoracic Goiter (IG) leads him to propase a revised clase sification and a useful grouping of the various forms of this disease. Their topography and relationships -in particular with the inferior laringeal nerve- are basic concepts. Most patients are women between 30 and 60 years of age ( 80 % ) . Visceral repercussions affect the respiratory sector, a fact which explains its clinical symptomatology; furthermore, knowledge thereof is necessary to the anesthesiologiest in deciding the technique to be employed.